Good Corporate Governance and Financial Performance: Does Leverage Matter? - Kholilah, Kholilah; Solikhah, Ramadhina Nur (Jurnal Akuntansi Terapan dan Bisnis, 2024)
This study aims to determine the effect of Good Corporate Governance on Financial Performance with Leverage as a moderating variable. The population used in this study are banking companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The sampling technique used was purposive sampling and obtained as many as 23 banking companies as a sample with 92 observations. The analytical method used is multiple linear regression analysis and MRA. The results of this study partially show that in 2018-2021 the Good Corporate Governance variable did not affect Financial Performance. The results of the study show that in 2018-2021 the Good Corporate Governance variable had significant effect on Financial Performance with Leverage as a moderating variable.